Tutela extrajudicial e dano estrutural ambiental ambiental no Brasil : Ministério Público e a efetividade do direito fundamental ao meio ambiente equilibrado - Gonçalves, Gabriel Sodré (2022)
This research aims to promote a new vision in search of solving old environment conflicts, whose effects have the potential to significantly interfere on the quality of human existence. The correct understanding about the origin of the damage, as well as the identification of the main triggers of the system that violates fundamental rights, are essential for a structural reform to prospectively solve the existing problem. Only through behavioral modification on the structure of institutions, offered by public policies or readjustments of conduct of entities and society, will it be possible to eliminate the cause of environmental damage and therefore give effectiveness to the fundamental right to a balanced environment. Using the hypotheticaldeductive method, making use of bibliographic research, it was possible to analyze the status of environmental degradation experienced in Brazil, as well as to tack concepts, characteristics, and essential elements for the resolution of environmental structural problems, a kind of classification of conflict that has received recent and voluminous attention from the Brazilian doctrine. Proceeding, the importance of the Brazilian Attorney General's Office for the promotion of the effectiveness of fundamental rights is discussed, while the questioning is launched about what is the most appropriate treatment to be given as a priority by the Agency in the alleged solution of environmental structural damages. In the end, by associating the characteristics of structural problems with the promotion of a resolutive action by the Attorney’s Generals Office, as well as taking into account that the resolution of such conflicts demands the necessary resignification, through the institution of public policies, of the violating structures that promote environmental degradation, it was possible to conclude that the selfcompositional extrajudicial environment endorses the best inaugural scenario to be adopted to face the issues, which will even make it possible to remove the criticisms related to judicial activism.Over and above that, once there is a successful extrajudicial approach, the social contribution will be enhanced by the timely and less traumatic implementation of the effectiveness of such an important fundamental right.